DESARROLLO DE UN RECUBRIMIENTO COMESTIBLE A BASE DEL EXTRACTO DE HIERBA LUISA (Cymbopogon citratus) Y MUCÍLAGO DE CACAO CCN-51 (Theobroma cacao L.) EN LA CONSERVACIÓN DE FRUTILLA (Fragaria × ananassa) - PINARGOTE MERA, JULY MARIBEL (2025)
The aim of this study was to develop an edible coating based on lemon verbena extract (Cymbopogon citratus) and CCN-51 cocoa mucilage (Theobroma cacao L.) to prolong the shelf life of strawberries (Fragaria × ananassa), evaluating its effect on fruit preservation